STRATEGI ORANG TUA KRISTEN DALAM MEMBANGUN DISIPLIN ANAK - Kosma Manurung (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2021)
This study intends to examine the strategies of parents in fostering child discipline in Christian families. The Bible places the primary responsibility for educating children on the parents. Children need discipline to shape their character. In addition, discipline is essential for children concerning social life, and discipline is the foundation children need to achieve their future. The method used is descriptive and literature review. The results show that parents play a role in building their children's discipline. They have to develop communication using the love language of their children by making themselves role models that can be emulated by their children, providing space for children to grow and explore themselves, and through action firm in love.